2017
DOI: 10.1007/978-3-319-69838-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Getting Buy-In for Climate Change Adaptation Through Urban Planning: Climate Change Communication as a Multi-way Process

Abstract: The purpose of this chapter is to evaluate the role of communication in building support for climate change adaptation through urban spatial planning. We take Durban in South Africa as our case study, a city with significant vulnerability to climate change which is widely regarded as having successfully implemented climate adaptation initiatives through spatial planning, despite a challenging socioeconomic context. In particular, we aim to assess the role of communication in initiating and sustaining Durban's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…First, both pilots highlighted the importance of project buy-in from government and local stakeholders. Stakeholder engagement at the start of a project has been found to increase success and sustainability of climate adaptation projects (Mabon and Shih, 2017). In the pilot studies, while informal project buy-in from government ministries and key civil society organizations and universities was achieved, the research team found that formalizing this support could have improved the legitimacy of these assessments.…”
Section: Lessons Learned From Protocol Implementationmentioning
confidence: 99%
“…First, both pilots highlighted the importance of project buy-in from government and local stakeholders. Stakeholder engagement at the start of a project has been found to increase success and sustainability of climate adaptation projects (Mabon and Shih, 2017). In the pilot studies, while informal project buy-in from government ministries and key civil society organizations and universities was achieved, the research team found that formalizing this support could have improved the legitimacy of these assessments.…”
Section: Lessons Learned From Protocol Implementationmentioning
confidence: 99%
“…RIBA has advocated for the architect's role as "visual communicator and enabler of good design decisions" for over a decade. Many researchers have since explored how investing in more effective and dynamic modes of public communication strengthens civic trust, allowing for more meaningful and longstanding improvements in urban equity to occur as a result (Mabon and Shih, 2018;Lin and Geertman, 2019;Åström, 2020).…”
Section: Worldbuilding and Co-productionmentioning
confidence: 99%
“…CBD, 2018b). 'Communication' is increasingly understood as a multi-way dialogue between different sections of society on what the most appropriate form of BES management is, rather than the one-way flow of information from 'experts' out to society (Mabon and Shih, 2018b). One aspect of evaluating CEPA may thus be the extent to which stakeholders have opportunity to meaningfully participate in decision-making processes (Wesselink et al, 2011).…”
Section: Communication Education and Public Awarenessmentioning
confidence: 99%